Flipped classroom to teach digital skills during Covid-19 - Maria Pilar Molina-Torres (OmniaScience, 2024)
This paper deals with the implementation of flipped learning as a didactic method and its use through the Moodle platform. For this purpose, a quantitative research was carried out with the intention of analyzing the perceptions of new teachers in the acquisition of digital competences that they acquire during their teaching and learning process. The sample is made up of three groups of students in the subject Didactics of Social Sciences in the third year of primary education. The results obtained show that active learning methodologies promote digital literacy in higher education and the improvement of good teaching practices. In this way, through this research, students updated their use of new educational platforms, given the lack of initial training in digital literacy. In short, we can conclude that flipped learning is a useful and innovative teaching method that combines face-to-face and online learning for the education and training of new teachers.